3-D Printed Lattice Core for Wide Angle Scanning Radome at X-Band - Yoon, Daeyeong; Na, Dong Yeop; Park, Yong Bae (IEEE Access, 2023)
In this paper, we introduce a 3-D printed lattice core for wide-angle scanning radome operating in the X-band. We explain the fundamental design methodology of the sandwich structure for radome and outline the technique to represent the 3-D printed core in terms of its effective dielectric constant. Our study further delve into the electrical characteristics of the unit cell, focusing on its performance with varying incident angles within the X-band. Utilizing 3-D printing technology, we fabricate the sandwich structure and measure its transmittance through the free-space measurement method. Our designed structure achieve a transmittance exceeding 77% for incident angles up to 45 degrees. We fabricate and measure six distinct samples, and the compiled data is present in a table. The findings highlight the high electrical performance of the sandwich structure and demonstrate its suitability for X-band wide-angle scanning applications.
Keywords: Design Methodology; Effective dielectric constants; Electrical characteristic; Fundamental design; Incident angles; Lattice; Unit cells; Wide angle scanning; X bands; 3-D printer; lattice; periodic structure; Radome; wide angle scanning